Awe and meaning: Elucidating complex effects of awe experiences on meaning in life. (3rd July 2019) - Rivera, Grace N.; Vess, Matthew; Hicks, Joshua A.; Routledge, Clay
Abstract: Research on the experience of awe suggests that awe has positive impacts on outcomes like life satisfaction and belongingness. No published work, however, has reported effects of awe on the experience of meaning in life. We reasoned that awe might have complicated effects on meaning. On the one hand, many awe experiences likely contain a positive flavor that contributes to both awe and general positive affectivity (happiness). Positive affectivity has a robust positive effect on meaning in life, suggesting that positive awe experiences might increase meaning. At the same time, however, awe experiences lead to a diminished self that reflects feelings of smallness and insignificance, which might negatively predict meaning. We thus hypothesized that awe experiences can, in some contexts, produce competing indirect effects on judgments of meaning in life through happiness and small‐self feelings. The results of five studies ( N  =   1, 690) supported these predictions.